Stress Testing the University Fall Break Policy: Understanding the Impact on Student Mental Health - Pilato, Kelly A.; Law, Madelyn P.; Hay, John A.; Narushima, Miya; Moore, Shannon A. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Attempting to support student mental health, many Canadian universities have implemented a fall break with the assumption it would be helpful in alleviating students’ stress and anxiety. However, there is no baseline data regarding stress level or mental illness burden of students to understand its effectiveness. Using case study methodology with mixed methods, this research sought to appraise, given a lack of baseline data, the impact of a fall break on student mental health. While the surveys revealed that students overwhelmingly liked the break and perceived it to reduce their school related stress, the focus groups revealed key insights into understanding stress and coping among university students about how students like to de-stress that have practical implications for any policy aimed at promoting students’ mental wellness. This research offers practical policy suggestions to help post-secondary institutions determine whether a fall break week can be effective in addressing students’ stress and anxiety.